(untitled) (Research, Society and Development, 2020)
The study has as its theme child microcephaly and its relationship with the Zika virus because it understands that risk factors can influence the prevalence of children with microcephaly. The objective was to conduct an integrative review on childhood microcephaly and see if there is a relationship with the Zika virus. For the selection of the sample, criteria were defined for articles indexed from 2015 to 2020 published in national and international journals. Data collection was performed in the database SCIELO, Pubmed and Google Scholar using the following descriptors: microcephaly, child, prevalence and Zika Virus. The search resulted in 15 articles and after using the inclusion and exclusion criteria, 8 articles remained for analysis, interpretation and discussion. It was observed that in the analyzed studies there was a great increase in the number of cases of microcephaly in Brazil, showing a link with contamination by the Zika virus. We conclude that there is a relationship between the increase in microcephaly case reports and the Zika virus epidemic, mainly in northeastern Brazil. It was shown that the lack of information on the related risk factors can be the gateway to the development of microcephaly, having to do with the lifestyle and the socioeconomic situation.